Acculturation Preferences, Ethnic and Religious Identification and the Socio-Economic Adaptation of Russian-Speaking Immigrants in Belgium. Issue 6 (2nd November 2017) - Grigoryev, Dmitry; Berry, John W.
Abstract: This study tests a model of the socio-economic adaptation (SEA) of Russian-speaking immigrants in Belgium. It examines the roles of language skills and length of stay in Belgium, and of ethnic and religious identification in their acculturation preferences in their adaptation. The study showed that language skills were positively related to preferences for integration and assimilation, while length of stay was negatively related to separation. In turn, integration and assimilation predicted higher SEA, and separation predicted lower adaptation. Ethnic and religious identification also played a role. In sum, more orientation toward the host society (integration and assimilation) promoted better adaptation.